ISOLATION, CHARACTERIZATION AND ANTIBIOTIC SUSCEPTIBILITY TESTING OF ENTERIC BACTERIA ISOLATED FROM URINARY TRACT INFECTIONS - TANUJA RANA; JASUMATI; NAVROOP KAUR; PAYAL THAKUR (International Journal of Pharma and Bio Sciences, 2013)
Urinary tract infections (UTIs) are the most common type of infections caused by bacteria. The aim of the present study was to investigate the type of bacterial pathogens present in UTIs and to check their antibiotic sensitivity. In the present study, a total of 60 urine samples were taken, Out of which 8 were of males including 1of child and 52 were of females. The urine samples were cultured on MacConkey agar and incubated, which resulted into the formation of Lactose Fermenting/Non Lactose Fermenting (LF/NLF) type of colonies. After morphological characterization, different urinary tract pathogens were identified by biochemical tests and inoculated on selective media for final confirmation. Out of 8 samples of male, 6 were positive and out of 52 female samples 25 were positive. It is found that the age group most affected was of 21-40 and the organism most commonly encountered was E.coli. The six antibioticswere used to test the antibiotic susceptibility pattern of isolated strains. Maximum isolates were resistant to Ceftazidime & Amikacins.